Penyuluhan Penggunaan dan Pencegahan Pengaruh Gadget di Rumah Tangga - Salim, Agus (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
This activity aims to increase understanding and knowledge about gadgets. Advances in Technology and Information affect many aspects of human life, including economics, laws, health, and education. The existence of technology provides convenience in various activities of humans; however, it replaces human labor too. Likewise, the advancement of digital-based information enables humans to access information from anywhere at any period, while the most current information moves quickly. The presence of Technology and Information must be accompanied by human ability. Ability to use well and filter information effectively. The sophistication of technology and the speed of information should be accompanied by the ability to use it, which aims to use various technological products in learning activities. Thus, teachers can teach using technology products such as e-books, animations, slides, and videos. However, humans have numerous opportunities to use technology products to make things that go against the good intentions of technological and information inventions. For this reason, before and while using technology and reading the information, every technology user must obtain an education. Keywords: gadget, technology, education